Mewujudkan Keadilan Struktural: Kontekstualisasi Hadis Perampasan Tanah Perspektif Hans Georg Gadamer - Aji Pangestu; Rizky Yazid; Lisfa Sentosa Aisyah (Prophetica: Journal of Hadith Studies, 2025)
Classical scholars interpreted the hadith warning that “whoever wrongfully takes a handspan of land will have seven layers of earth fastened around his neck on the Day of Judgment” primarily as an eschatological and moral admonition addressed to individual wrongdoers. This reading, while spiritually rich, tends to confine the hadith’s universal significance to personal ethics. This article recontextualizes the hadith so that it speaks to contemporary agrarian injustice. Using library research and the philosophical hermeneutics of Hans-Georg Gadamer—drawn from Truth and Method and Philosophical Hermeneutics—the study traces three operations: historically-effected consciousness (Wirkungsgeschichte), the fusion of the textual and the reader’s horizons (Horizontverschmelzung), and the formation of shared understanding. The analysis finds that the textual horizon foregrounds theological and legal concerns, while the reader’s horizon, informed by historical materialism, reads the hadith as a prophetic response to structural agrarian inequality, a rejection of land monopoly, and an argument for just land ownership. The article argues that the hadith functions not merely as a spiritual warning but as an ethical-political manifesto supporting just agrarian policy and grassroots movements protecting the land rights of marginalized communities, while remaining rooted in its prophetic spirit.